Measurement of Switching Latency in High Data Rate Ethernet Networks - Hegr, Tomas; Voznak, Miroslav; Kozak, Milos; Bohac, Leos (Elektronika ir Elektrotechnika, 2015)
The paper deals with a methodology of switching latency measurement in switched Ethernet networks. The switching latency is parameter necessary for simulation and design of low-latency networks that are often intended for real-time control inherent to many industrial applications. The proposed measurement methodology provides a simple way of switching the latency determination and vendor quoted latency values verification directly at the physical layer. Numerous experimental measurements were carried out to support the arguments in this paper and to demonstrate the usability of the proposed methodology. All results are presented and analysed up to 10GBase-R Ethernet including OpenFlow switches. DOI: http://dx.doi.org/10.5755/j01.eee.21.3.10445